Evaluation of Overall Seismic Performance of RC Structures and Effectiveness of Seismic Isolation Technology Under Extreme Events: February 6, 2023, Earthquakes - Yenidogan, Cem (MDPI, 2025)
Two large earthquakes with a series of aftershocks struck southeastern T & uuml;rkiye within 9 h and had catastrophic consequences. Following the earthquake doublet, 11 provinces corresponding to approximately 1/7 of T & uuml;rkiye were declared disaster zones. Even though the epicenters of the first event and second mainshocks were in Pazarcik and Elbistan with a magnitude (Mw) of 7.7 and 7.6 with over 500 km of multiple-fault ruptures, Hatay province was the most heavily damaged province and had the highest number of casualties and collapsed buildings. A densely deployed strong ground motion array of the Disaster and Emergency Management Presidency of Turkey (AFAD) recorded the earthquake doublet of the two consequent mainshocks, including ground motions exhibiting near-fault features. A suite of recorded ground motions in Hatay province is incorporated to examine the destructiveness of ground motions on reinforced concrete Moment-Resisting Frame buildings and the effectiveness of seismic isolation technology to reduce the observed damage. Moreover, Turkish Seismic Design Code-2018 code provisions are elaborated to determine the characteristics of the investigated structures. Nonlinear response history analyses were conducted for 24 types of structures by following the design provisions. The inelastic hysteretic response features in the fixed-base and isolation systems are represented through an inelastic Single-Degree-of-Freedom Bouc-Wen hysteretic model. Extreme characteristics of near-fault ground motions on RC structures and seismically isolated systems resulted in excessive drift and displacement demands. Roof drifts of reinforced concrete Moment-Resisting-Frame buildings exceeded 4% roof drift in mid-rise buildings, compatible with the field observations in Antakya city center, where the displacement demand and ultimate base shear coefficient of seismically isolated structures considered in this study exceeded the elastic spectral coefficient values of the design spectrum in the proximity of fault ruptures.
Keywords: February 6, 2023; T & uuml; rkiye-Syria earthquake; moment-resisting frame; seismic isolation; TSDC-2018; reconnaissance study; Bouc-Wen hysteretic model; FAULT GROUND MOTIONS; RANDOM VIBRATION; DESIGN; EAST; VELOCITY; Construction & Building Technology; Engineering